ISOLASI DAN UJI KEMAMPUAN BAKTERIOFAG SEBAGAI AGENS PENGENDALI PENYAKIT LAYU BAKTERI (Ralstonia solanacearum) PADA TANAMAN TOMAT - Abdul Choliq, Fery; Martosudiro, Mintarto; Istiqomah, Istiqomah; Fanhash Nijami, Muhammad (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2020)
Tomato is the top priority in the development of horticultural crops. The obstacle which mostly encountered is Ralstonia solanacearum pathogen attack. Bacteriophage can cause bacterial lysis after they they develop themselves inside the bacteria. The specific of the bacteriophage can provide result quickly, accurately, and efficiently so that it can be used as an alternative to control bacterial wilt disease R. solanacearum environmentally friendly. This study aims to find out the effectiveness of bacteriophage to control the bacterial wilt disease R. solanacearum. The testing method are plaque assay, bacteriophage infections test in various dilutions, bacteriophage infection test in a liquid medium, and transmission electron microscopy test. In the greenhouse scale testing using a Completely Randomized Design (CRD) with 6 treatments and 4 replications. Quantitative data were analyzed using analysis of variance 5% error level and followed by least significant different test level of 5%. The results showed that bacteriophages can infect R. solanacearum. Bacteriophage can infect bacteria R. solanacearum indicated by the appearance of plaques in NA media, the declining value of absorbance spectophotometer, and can lyse bacterial cells from dilutions 10-1 to 10-9. The morphology of bacteriophages that infect R. solanacearum have hexagonal head structure and it have which is with a size of 200 nm. In the greenhouse scale showed that the symptoms of R. solanacearum appear at 29 days after inoculation. Application of bacteriophages can control R. solanacearum with lower percentage than the control treatment.